The Economic Diversification Strategy and its Impact on Economic Growth in the Kingdom of Saudi Arabia - Shehata, Gaber Ahmed Bassyouni; Ibrahim, Amr Eldaba; Ahmed, Iman Ali Abdel Salam (Advances in Social Sciences Research Journal, 2026)
Energy is considering of modern life, essential for operating all sectors and managing daily affairs. It is a vital resource that nations strive to secure, whether for powering factories, transportation, or other energy-intensive activities that contribute to human production. Energy comes in diverse forms, including oil, coal, gas, and renewable sources such as solar, wind, and hydroelectric power. The research is based on a descriptive analytical methodology that combines a literature review and data analysis using linear regression models and time series analysis, with data processing via Excel, SPSS, and E-Views programs to conduct accurate statistical analyses and test hypotheses at significance levels of 0.01 and 0.05. The study is limited in time to two periods (2000-2008) and (2015-2024) coinciding with influential economic crises, and in terms of location to the Kingdom of Saudi Arabia. Data collection is based on official sources such as the World Bank, the Saudi Ministry of Finance, the General Authority for Statistics, OPEC, and the US Energy Information Administration, in addition to previous studies and relevant references. Two main hypotheses were put forward: that there is no statistically significant relationship between the economic diversification strategy and the gross domestic product, and that there is no statistically significant relationship between the average annual oil price and the GDP growth rate. The research aims to identify the economic diversification strategies followed by the Kingdom and measure their effectiveness in expanding the production base, reducing the impact of oil price fluctuations, and achieving sustainable economic development. It also seeks to analyze the relationship between oil price volatility and economic growth in the Kingdom of Saudi Arabia. The most important findings of the research were: - The results generally show that some sectors contribute to GDP growth, albeit with a relatively small contribution compared to the oil sector, given Saudi Arabia's heavy reliance on it. This demonstrates the dominance of oil sector revenues and profits in driving GDP growth. - The agricultural sector's value added had a very significant positive impact on GDP during the period 2000-2008, and this positive impact is also expected to continue during the period 2015-2024. - The added value of the industrial sector had a significant positive impact on GDP during the period 2000-2008, but no statistically significant impact was observed between 2015 and 2024. - Exports and imports had no statistically significant impact on GDP during the period 2000-2008, and the value added of exports and imports also had no statistically significant impact on GDP during the period 2015-2024. - Thus, the study proved the first hypothesis incorrect, which states that there is no statistically significant relationship between the economic diversification strategy and a set of economic variables (economic growth, production rates, national consumption volume, and national investment volume) in the Kingdom of Saudi Arabia. - No statistically significant impact of oil price, investment rate, and consumption rate on GDP during the period (2000-2008). - A very significant positive impact of oil price on GDP during the period (2015-2024). - A significant positive impact of consumption rate on GDP during the period (2015-2024). - No statistically significant impact of investment rate on GDP during the period (2015-2024). Thus, the study disproved the second hypothesis, which stated that there is no statistically significant relationship between the average annual price of a barrel of oil and the annual GDP growth rate in the Kingdom of Saudi Arabia